Cross-Agencies And Community Collaboration For Tourism In Lebak Regency, Banten Province, Indonesia - Khie, Sak; Lindawati, Lindawati (JURNAL DESTINASI PARIWISATA, 2022)
Tourism is the leading sector in Lebak Regency to encourage economic growth. However, the Covid-19 pandemic affects tourist visits and the growth of businesses and SMEs. This study described tourism promotion innovations in Lebak Regency, Banten Province, Indonesia, namely the Lebak Regency Calendar of Events (CoE). A case study was used, with literature reviews and interviews to collect data. The CoE was in line with the annual development plan, which began with the Development Planning Conference (Musrenbang) and the framing of Local Government Work Plans (RKPD). The culture and tourism agency took the role of 'packaging' and synchronised each agency's programme in Lebak Regency as tourism events or facilitated as part of the tourism events. Each tourism event in Lebak Regency involved various agencies and sectors, the arts community, creative economy actors, and SMEs in Lebak Regency. This innovation encourages tourism promotion massively in Lebak Regency to increase tourist visits and reactivate community economic activity. Keyword: Development Program, Economic Growth, Innovation, Tourism